The Role of ARID1A in Tumors: Tumor Initiation or Tumor Suppression? - Xu, Shouying; Tang, Chao (Frontiers in Oncology, 2021)
Genes encoding subunits of SWItch/Sucrose Non-Fermenting (SWI/SNF) chromatin remodeling complexes are collectively mutated in 20% of all human cancers, among which the AT-rich interacting domain‑containing protein 1A (ARID1A, also known as BAF250a, B120, C1orf4, Osa1) that encodes protein ARID1A is the most frequently mutated and mutations in ARID1A have been found in various types of cancer. ARID1A is thought to play a significant role both in tumor initiation as well as in tumor suppression, which is highly dependent upon context. Recent molecular mechanistic researches have revealed that ARID1A participates in tumor progression through its effects on control of cell cycle, modulation of cellular functions such as EMT and regulation of various signaling pathways. In this review, we synthesize a mechanistic understanding of the role of ARID1A in human tumor initiation as well as in tumor suppression and further discuss the implications of these new discoveries for potential cancer intervention. We also highlight the mechanisms by which mutations affecting the subunits in SWI/SNF complexes promote cancer.